A SURVEY ON FARMERS’ AWARENESS OF DANGERS ASSOCIATED WITH THE USE OF ANTIMICROBIAL AGENTS IN FISH HATCHERIES, IJEBU-ODE, NIGERIA - DUROJAIYE, A.F; BALOGUN, T.E.; SULE, S.O.; OJETAYO, T.A.; AKINTUYOLE, S.A. (Nigerian Journal of Fisheries, 2020)
The study assessed the level of awareness of farmers on the dangers associated with the use of antimicrobial agents in fish hatcheries. Thirty-six fish hatcheries farmers were randomly selected for the survey using structured questionnaire. The questionnaire was used to gather information on the socio-demographic characteristics of farmers, pattern of application of antimicrobial agents and the level of awareness of farmers on dangers of use of antimicrobial agents. Descriptive statistics was used to analyze the results. The result showed that both males and females were involved in fish hatchery practices and all the farmers had one form of education or the other. Antimicrobial agents were administered by 85.71% of the farmers themselves without the supervision of an authorized personnel with 64% applying them prophylactically. The mode of application of antimicrobial agents is through water, in-feed application, and injection. About 42% gave no response on whether they think indiscriminate use of antimicrobials in fish hatcheries is dangerous while 38.71% believe it is dangerous. This indicates that the awareness level of most of the farmers is low. Hence, there is need for adequate sensitization of farmers on the dangers associated with the use of antimicrobial agents in fish health management.